Students’ self-assessment in Physical Education Teacher Training. A comparison with other published experiences (Praxis Educativa, 2012)
This paper shows a self-assessment experience from students in PETE (Physical Education Teacher Education) in Argentina and its relationship with similar experiences in U.S.A. and Spain. In the first place there is a description of the experience which is later compared with different authors’ conclusions and findings with which we worked in our context.
Keywords: self-assessment; education; democratic values